Expression of Regional Memory in Lithuania in 1918–1940: Two Cases of Samogitia - Mačiulis, Dangiras (Acta humanitarica academiae Saulensis, 2025)
In Lithuania in 1918–1940 it is possible to state the aspirations to strengthen the Samogitian region and the Samogitian identity. The strengthening of the Samogitian identity had to be accompanied by the creation of a Samogitia/Samogitian regional memory culture. The article seeks to answer the questions: whether there have been targeted efforts to form a regional Samogitia/Samogitian memory culture and what signs confirm these processes in the public space. In search of answers to these questions, two case studies were carried out, the objects of which were selected: the Samogitian museum “Alka” and the monument “Žemaitis” built in Raseiniai.Based on the case studies, it is stated that there were purposeful efforts to form a regional Samogitia/Samogitian memory culture. This was due to the perception of the representatives of the regional elite with a Samogitian identity that Samogitian identity is not possible without a culture of memory that confirms and supports it. It is recognized that the regional memory culture of Samogitia needs institutions representing it, for example, a museum, whose expositions will embody the narrative of Samogitian history and it will help to maintain and establish Samogitian identity. The process of formation of Samogitian memory culture is witnessed by the manifestations of this culture with the help of monuments in public space. This expression is confirmed by the monument “Žemaitis” built in Raseiniai. This monument, with the help of a depersonalized Samogitian peasant image, presented a historical narrative about how in the 19th century during the national revival, the awakened nation restored the state of Lithuania through armed struggles and the Samogitians were active participants in this historical process. At the same time, the monument told the history of Lithuania in recent times and the role of Samogitia/ Samogitians in this history. It can be as an example of how regional and national historical narratives intertwine and how a regional memory culture is formed under the influence of a national memory culture.
Keywords: regional memory; Samogitia; Samogitian memory culture; Samogitian museum “Alka”; Vincas Grybas